Manajemen Program Life Skill (English Class) dalam Meningkatkan Kompetensi Berbahasa Siswa di MAN 2 Pangandaran - Pipin Pitriyani (J-STAF: Siddiq, Tabligh, Amanah, Fathonah, 2025)
In the current era of globalization, education must be made number one and primary in life's needs, because education is very much needed in order to improve the quality of human resources that can and are able to compete in the era of globalization. Therefore, to answer the challenges in this era of globalization, educational institutions need and must carry out innovations that are able to produce highly competent students, one of which is by having a special school program such as providing life skills, because with a life skills program at least students have the provision and basics about how to face the challenges of the times. This research uses a qualitative method, using a descriptive approach, in this case observing the management of the life skills program (English class) in improving students' language competence at MAN 2 Pangandaran. This research uses data collection techniques by means of interviews, observation and documentation. The primary data in this research are life skills managers, student affairs leaders and MAN 2 Pangandaran teachers. Secondary data consists of theoretical data, documentation data and other supporting data obtained from school documents. The data wettability test was carried out by source triangulation. Data analysis in this research uses data reduction, data presentation, and drawing conclusions. The research results show that: management of the life skills program (English Class) in increasing student competence, namely through planning, organizing, implementing and monitoring, is able to increase student competence. Students' ability in English has increased and what is quite encouraging for the management and the school is that students who take part in Life Skills (English Class) can excel at the district level by winning the English speech competition at the Pangandaran district level. This achievement can be used as a starting point. measure the success of the life skills program (English Class) in improving students' language competence.